Symbol Digit Modalities Test: Normative data for Spanish-speaking pediatric population - Arango-Lasprilla, JC; Rivera, D; Trapp, S; Jiménez-Pérez, C; Hernández Carrillo, C L; Pohlenz Amador, S; Vergara-Moragues, Esperanza; Rodríguez-Agudelo, Y; Rodríguez-Irizarry, W; García de la Cadena, C; Galvao-Carmona, A; Galarza-del-Ángel, J; et al. (NeuroRehabilitation, 2017)
OBJECTIVE: To generate normative data for the Symbol Digit Modalities Test (SDMT) in Spanish-speaking pediatric populations. METHOD: The sample consisted of 4,373 healthy children from nine countries in Latin America (Chile, Cuba, Ecuador, Guatemala, Honduras, Mexico, Paraguay, Peru, and Puerto Rico) and Spain. Each participant was administered the SDMT as part of a larger neuropsychological battery. SDMT scores were normed using multiple linear regressions and standard deviations of residual values. Age, age2, sex, and mean level of parental education (MLPE) were included as predictors in the analyses. RESULTS: The final multiple linear regression models showed main effects for age in all countries, such that score increased linearly as a function of age. In addition, age2 had a significant effect in all countries, except in Honduras and Puerto Rico. Models indicated that children whose parent(s) had a MLPE >12 years of education obtained higher score compared to children whose parent(s) had a MLPE ≤12 years for Chile, Guatemala, Mexico, and Spain. Sex affected SDMT score for Paraguay and Spain. CONCLUSIONS: This is the largest Spanish-speaking pediatric normative study in the world, and it will allow neuropsychologists from these countries to have a more accurate interpretation of the SDMT with pediatric populations.
Keywords: Symbol Digit Modalities Test; neuropsychology; spanish-speaking populations; pediatric population; JCR; Scopus